In situ effect of chewing gum containing CPP–ACP on the mineral precipitation of eroded bovine enamel—A surface hardness analysis - Prestes, Letícia; Souza, Beatriz M.; Comar, Lívia P.; Salomão, Priscila A.; Rios, Daniela; Magalhães, Ana Carolina (Journal of dentistry, 2013)
Stimulation of salivary flow is considered a preventive strategy for dental erosion. Alternatively, products containing calcium phosphate, such as a complex of casein phosphopeptide–amorphous calcium phosphate (CPP–ACP), have also been tested against dental erosion. Therefore, this in situ study analyzed the effect of chewing gum containing CPP–ACP on the mineral precipitation of initial bovine enamel erosion lesions. Twelve healthy adult subjects wore palatal appliances with two eroded bovine enamel samples. The erosion lesions were produced by immersion in 0.1% citric acid (pH 2.5) for 7min. During three experimental crossover in situ phases (1 day each), the subjects chewed a type of gum, 3 times for 30min, in each phase: with CPP–ACP (trident total), without CPP–ACP (trident), and no chewing gum (control). The Knoop surface microhardness was measured at baseline, after erosion in vitro and the mineral precipitation in situ. The differences in the degree of mineral precipitation were analyzed using repeated measures (RM-) ANOVA and post hoc Tukey's test (p<0.05). Significant differences were found among the remineralizing treatments (p<0.0001). Chewing gum (19% of microhardness recovery) improved the mineral precipitation compared to control (10%) and the addition of CPP–ACP into the gum promoted the best mineral precipitation effect (30%). Under this protocol, CPP–ACP chewing gum improved the mineral precipitation of eroded enamel. Since the prevalence of dental erosion is steadily increasing, CPP–ACP chewing gum might be an important strategy to reduce the progression of initial erosion lesions.